Cross-sectional seroprevalence study of bovine herpesvirus 1, bovine respiratory syncytial virus, and parainfluenza virus 3 in cattle from Villavicencio, Colombia - Catalina Ballesteros González; Karen Briñez; Julio César Tobón; Danny Wilson Sanjuanelo Corredor; Fernando Vicosa Bauermann; Blanca Lisseth Guzmán Barragán (BMC Veterinary Research)
Abstract Background Bovine respiratory disease complex (BRDC) is a widely distributed and multifactorial syndrome, leading to significant economic losses to the cattle industry. Many viruses are considered causative agents of BRDC, including bovine herpesvirus 1 (BoHV-1), bovine respiratory syncytial virus (BRSV), and parainfluenza virus 3 (PI-3). This study aimed to determine the seroprevalence of BoHV-1, BRSV, and PI-3 in serum samples collected from cattle in Villavicencio, Colombia. A total of 725 animals from 29 herds were sampled and tested for BoHV-1 and BRSV using ELISA. For PI-3, 440 animals were selected from 24 herds and tested using ELISA. An epidemiological survey collected information on animal characteristics, management practices, health, and environmental factors. Seroprevalence rates for each disease were determined, and a bivariate analysis was performed using a contingency table with odds ratios and Pearson’s Chi-square test. Results The seroprevalence rates were 44.9% for BoHV-1, 94.3% for BRSV, and 85.9% for PI-3. At the herd level, the seroprevalence was above 95% for all tested viruses. Two simultaneous risk factors for all three diseases were identified: female sex and age over 3 years. The risk factors for BoHV-1 were the sale of animals, purchase of animals, history of abortions, and Brahman breed. Conversely, artificial insemination was a protective factor. For BRSV, the purchase of animals was a risk factor, and the history of abortions correlated to PI-3 seropositivity. No significant correlation between the three diseases was identified. Conclusions This study confirms the high prevalence of BoHV-1, BRSV, and PI-3, underscoring the need for preventive measures against these non-officially notified diseases in Colombia.